2022
DOI: 10.3389/fpsyg.2021.788586
|View full text |Cite
|
Sign up to set email alerts
|

From Habit-Forming to Habit-Breaking Availability: Experiences on Electronic Gambling Machine Closures During COVID-19

Abstract: Electronic gambling machines (EGMs) are among the most harmful forms of gambling. The structural characteristics of EGMs prolong and reinforce gambling similarly to other habit-forming technologies. In Finland, the wide availability of EGMs in non-casino locations is likely to further reinforce the habit-creating nature of gambling offer by incorporating EGMs into everyday practices. The COVID-19 pandemic changed the landscape of gambling in Finland. The most visible change was the closure of land-based EGMs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This was particularly connected to increases in online gambling. Previous evidence from the Finnish context has indicated that while there were no important shifts from land-based gambling to online gambling during the pandemic, there was an intensification in gambling behaviour for some who were already playing predominantly online before COVID-19 (Marionneau and Järvinen-Tassopoulos, 2022;. Family members had made similar observations.…”
Section: Impacts Of Covid-19 On Gambling Behaviour and Harmsmentioning
confidence: 85%
See 1 more Smart Citation
“…This was particularly connected to increases in online gambling. Previous evidence from the Finnish context has indicated that while there were no important shifts from land-based gambling to online gambling during the pandemic, there was an intensification in gambling behaviour for some who were already playing predominantly online before COVID-19 (Marionneau and Järvinen-Tassopoulos, 2022;. Family members had made similar observations.…”
Section: Impacts Of Covid-19 On Gambling Behaviour and Harmsmentioning
confidence: 85%
“…As a result, the levels of gambling consumption and related harms were reduced among those gambling in land-based environments (for example, Brodeur et al, 2021;Hodgins and Stevens, 2021). For many of those who engaged in online gambling before the pandemic, the pandemic also translated to increased gambling participation and harm (Gainsbury et al, 2021;Hodgins and Stevens, 2021;Xuereb et al, 2021;Marionneau and Järvinen-Tassopoulos, 2022;Shaw et al, 2022). At the same time, the social distancing measures increased time spent at home with the family.…”
Section: Introductionmentioning
confidence: 99%